Rolle der neoadjuvanten Strahlentherapie beim Rektumkarzinom: Ist die MRT-basierte Selektion ein Zukunftsmodell? = Role of neoadjuvant radiotherapy for rectal cancer : IsMRI-based selection a futuremodel? - Kulu, Yakup; Hackert, Thilo; Debus, Jürgen; Weber, Marc-André; Büchler, Markus W.; Ulrich, Alexis (Der Chirurg, 2016)
Following the introduction of total mesorectal excision (TME) in the curative treatment of rectal cancer, the role of neoadjuvant therapy has evolved. By improving the surgical technique the local recurrence rate could be reduced by TME surgery alone to below 8 %. Even if local control was further improved by additional preoperative irradiation this did not lead to a general survival benefit. Guidelines advocate that all patients in UICC stage II and III should be pretreated; however, the stage-based indications for neoadjuvant therapy have limitations. This is mainly attributable to the facts that patients with T3 tumors comprise a very heterogeneous prognostic group and preoperative lymph node diagnostics lack accuracy. In contrast, in recent years the circumferential resection margin (CRM) has become an important prognostic parameter. Patients with tumors that are very close to or infiltrate the pelvic fascia (positive CRM) have a higher rate of local recurrence and poorer survival. With high-resolution pelvic magnetic resonance imaging (MRI) examination in patients with rectal cancer, the preoperative CRM can be determined with a high sensitivity and specificity. Improved T staging and better prediction of the resection margins by pelvic MRI potentially facilitate the selection of patients for study-based treatment strategies omitting neoadjuvant radiotherapy.